STUDI PEMBINAAN HUMAN RELATIONS PADA KANTOR CAMAT KECAMATAN ROKAN IV KOTO KABUPATEN ROKAN HULU - Harmazaldi Harmazaldi; Parjiyana Parjiyana (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
This study aimstodetermine the level of development of human relations at the District Office District of Rokan IV Koto Rokan Hulu. Assessment indicator sused includea pleasant working at mosphere, reasonable informality inemploymentrelations, capacity building subordinateto themaximum level, the researchon theexistence ofthe destination location carefully. There recognition and appreciation for the execution of a job well done, and the remuneration should becom mensurate with the services rendered. This type of resear chislocatedat the District Office District of Rokan IV Koto Rokan Hulu is adescriptivesurvey, namelya questionnaireasa tool to prioritizethe list ofdata collection and data collected by the tool is the nused asthe main raw material for analyzing the condition of the objectivity of empirical are populations and sample sinthis study are employees, totaling 26 people. Asampling techniqueusedin determiningthe individual sample iscensustechniques for employees. Type anddata collection techniq uesusedconsist of, primary data, collected by questionnai retechnique, andinterviewsas well assecondary data collected using observation techniques. While the data analysis techn iqueusedis to usea frequencytabletool. Based on this analysis techni quesresearchers assessand concludethatthe Human Relations Development Studies at the District Office District of Rokan IV Koto Rokan Huluis in the interval assessment done enough. Recommendations to be considered especially with respect to improvement of relations that must be tightenedagainto increase the organization's effectivenessin carrying outits duties and functions.